A docência no Instituto Federal – campus Itapetininga no contexto da verticalização do ensino: horizontes possíveis - Carvalho, Ana Carolina Medeiros Gatto Vieira (2023)
This work investigated how Professional and Technological Education Professors experience vertical education at the Federal Institute – Campus Itapetininga. The methodological approach of the research was configured from the Historical-Cultural Theory, specially in the "experience" concept proposed by Vigotski (1995, 2000, 2001). Data come from three primary sources: systematic mapping, document consultation, and interviews with professors. The results indicate that teaching is a profession that is constituted for the participants through their personal and professional experiences and their relationship with students and co-workers, enabling professional development. Training is considered necessary, but greater importance is given to previous experiences/knowledge in vocational training and sharing experiences with peers. Verticalization is understood as a formative itinerary between high school and graduate school, covering specificities in the different levels of education, difficulties, potentialities, and tensions resulting from this process. Concerning teaching at the Federal Institute, good working conditions are highlighted, such as remuneration, infrastructure, class hours, research and extension activities development, and positive relationships with students and colleagues. However, a few difficulties related to the verticalization of teaching in the IF are addressed, which, in general, are seen as a potentiality of the educational work. The teachers' experiences rescue subjective aspects and significant situations in professional practice. The investigation presents a proposal for a training path for these teachers. This work develops the "multifaceted teaching" concept, which seeks to portray the complexity of vertical teaching work in Federal Institutes. The study shows the training needed for Professional Education teachers, carried out in a planned and systematic way, and discusses the importance of the professional induction period in the EBTT teacher's career and collective spaces for continuing education, considering the teaching role in this vertical process.